D-Psicose increases energy expenditure and decreases body fat accumulation in rats fed a high-sucrose diet. (March 2014) - Ochiai, Masaru; Onishi, Kana; Yamada, Takako; Iida, Tetsuo; Matsuo, Tatsuhiro
Abstract We investigated the anti-obesity effects of d-psicose by increasing energy expenditure in rats pair-fed the high-sucrose diet (HSD). Wistar rats were divided into two dietary groups: HSD containing 5% cellulose (C) and 5% d-psicose (P). The C dietary group was further subdivided into two groups: rats fed the C diet ad libitum (C-AD) and pair-fed the C diet along with those in the P group (C-PF). Resting energy expenditure during darkness and lipoprotein lipase activity in the soleus muscle were significantly higher in the P group than in the C-PF group. Serum levels of glucose, leptin and adiponectin; glucose-6-phosphate dehydrogenase activities in the liver and perirenal adipose tissue; and body fat accumulation were all significantly lower in the P group than in the C-PF group. The anti-obesity effects of D-psicose could be induced not only by suppressing lipogenic enzyme activity but also by increasing EE in rats.